Etude de la conformation et la composition des oeufs chez deux souches de pondeuses industrielles (Isa f15, Cobb 500) - Choual Mustapha, Abd Essamad (My University, 2018)
This study was carried out in the region of Mostaganem whose main objective is to highlight the characteristics of the external and internal quality of eggs from two strains of industrial laying hens. A total of 67 eggs, divided into 32 eggs from the cobb 500 hens and 35 eggs from the Isa f15 strain, were collected and analyzed. Eggs from the cobb 500 strain showed significant superiority (p <0.001) for egg weight, endosperm weight, J/b ratio, and percentage of yolk compared to eggs derived from the strain ISA F15. On the other hand, for the parameters: shape index, Weight of the egg yolk, endosperm Height, Diameter of the egg yolk, Shell Thickness and Haugh Unit we did not observe any significant differences between the two groups studied. Our study shows that cobb 500 eggs have a better quantity of endosperm. As for the eggs from the ISA F15 strain which have a better quality of freshness.
Keywords: eggs; laying hens; industrial; strain; freshness.; oeufs; poules pondeuses; industrielles; souche; fraîcheur